RELIABILITY ANALYSIS FOR VIBRATION STABILITY OF DISC BRAKE SYSTEM WITH THЕ HYBRID PARAMETERS - HE Ning; ZHANG DeLong; ZHANG QingHua (Jixie qiangdu)
In view of the brake squeal suppression problem of automotive disc brakes during braking, the effects of brake imbalance and uncertainty in brake parameters, a stability and reliability analysis method of disc brake with the hybrid parameters was proposed by combining response surface methodology, finite element method, and reliability analysis theory. In this method . random, uncertain interval and fuzzy parameters were used to describe the dynamie characteristies of the brake system, and an unstable order response surface agent model of the disc brake system was established including random parameters, uncertain interval parameters and fuzzy parameters. Then, the remarkable affecting factors were obtained through sensitivity analysis of stability and reliability on brake system. Therefore, the influence laws of the second-order interaction of each factor were analyzed deeply based on stability and reliability analysis in Design Expert software. This method was used to verify the caliper disc brake of a certain type of automobile, and the results show that when the stability of the brake system with mixed parameters is not ideal, it can improve the stability of brake system effectively by increasing the thickness and elastie modulus of back plate of brake system.